Evolution mechanisms for goal-driven pattern families used in business process modelling. (16th January 2013) - Behnam, Saeed Ahmadi; Amyot, Daniel
Reusability is important when modelling business processes and patterns are known to increase reusability. A pattern-based framework that lays down a foundation for capturing knowledge about business goals and processes and customising it for specific organisations in a given domain is hence valuable. For many reasons however, the problems and solutions within a business domain are constantly changing. Consequently, such framework can be useful only if it provides mechanisms for evolving pattern families over time. In this paper, we propose and formalise four mechanisms for evolving a goal-driven pattern family targeting the modelling of business goals, business processes, and traceability links between these two views. We demonstrate the feasibility of the evolution algorithms with examples from the patient safety domain. We also illustrate how the framework is used to extract relevant business goals and processes in a specific healthcare context.